2016
DOI: 10.1097/pcc.0000000000000740
|View full text |Cite
|
Sign up to set email alerts
|

Early Electroencephalographic Background Features Predict Outcomes in Children Resuscitated From Cardiac Arrest*

Abstract: Objective To determine a) whether early electroencephalographic (EEG) background features were associated with survival and neurologic outcomes among children resuscitated from cardiac arrest and not treated with therapeutic hypothermia and b) if addition of EEG background to commonly used clinical criteria is more predictive of outcome than clinical criteria alone. Design Retrospective study. Setting Pediatric intensive care unit and Cardiac Intensive Care Units of a tertiary children’s hospital. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 50 publications
1
56
1
Order By: Relevance
“…Most electroencephalographic seizures have no clinical correlate and thus are not identified by clinical observation. (15, 20) Our study of 128 children post cardiac arrest undergoing EEG monitoring identified electrographic seizures in 15% of subjects. Electrographic status epilepticus occurred in 80% of subjects with seizures and was associated with unfavorable short-term neurologic outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Most electroencephalographic seizures have no clinical correlate and thus are not identified by clinical observation. (15, 20) Our study of 128 children post cardiac arrest undergoing EEG monitoring identified electrographic seizures in 15% of subjects. Electrographic status epilepticus occurred in 80% of subjects with seizures and was associated with unfavorable short-term neurologic outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…(28) This may be similar to the Overall Background Category which had substantial interrater agreement in this study and has been used in prior pediatric investigations. (2022, 33)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, absence of reactivity and worse EEG background scores are associated with increased odds of death and unfavorable neurologic outcomes after pediatric cardiac arrest [97,98].…”
Section: Post-arrest Electroencephalographymentioning
confidence: 99%
“…These include pupillary responses [98,118] serum biomarkers such as neuronspecific enolase and S100B [119,120] serum lactate levels [121], EEG findings [97,98], somatosensory evoked potentials [122], neuroimaging studies [123], non-invasive cerebral tissue oxygenation [105,124], and presence or absence of hypotension [94]. Importantly, the data supporting the application of these tools as prognosticators are not as robust in children as they are in adults, and each patient's overall clinical status after cardiac arrest must be considered over any one finding.…”
Section: Post-arrest Prognosticationmentioning
confidence: 99%